Våldets pedagogik: Krig och lek i svensk barnboksutgivning vid 1960-talets slut - Widhe , Olle (Tidskrift för litteraturvetenskap, 2013)
The Pedagogy of Violence. Children’s Literature in Sweden at the End of the 1960’s This article argues that the Vietnam War had a massive impact on children’s literature published in Sweden at the end of the 1960’s. Numerous children’s books portrayed the child as confronting the horrifying scenes from the Vietnam War through television news reports. These books indicate the need for a literature that in some way could explain the violence taking place in the surrounding world to small children. The examples provided in this article illustrate the scale of this impact but also the different ways in which authors dealt with the situation. The author’s choice of aesthetic form and genre was deeply influenced by political as well as pedagogical concerns following new conceptions of child care and child development. The understanding of the connection between, on the one hand, violence and aggression and, one the other, children and play was inspired by psychodynamic theories that offered new impulses to the discussion about the function of children’s literature. However, these conceptions of childhood, play and fantasy were to a considerable extent in conflict with not only the demand for a politically engaged and profoundly realistic literature but also the question of how much violence and darkness the young child could take in and deal with.